Exploring factors associated with hepatitis B screening in a multilingual and diverse population - Janet N. Chu; Tung T. Nguyen; Natalie A. Rivadeneira; Robert A. Hiatt; Urmimala Sarkar (BMC Health Services Research, 2022)
Abstract Background Racial/ethnic minorities bear a disproportionate burden of hepatitis B virus (HBV) infection and disease. Disparities in HBV screening contribute to worse outcomes for communities of color. We examined the impact of race/ethnicity, language preference, and having a usual place of care on HBV screening in a multilingual, urban cohort. Methods We used questions from the Health Information National Trends Survey and added validated questions about healthcare access and health literacy. We administered this survey in English, Spanish, and Chinese to a selected convenience sample of San Francisco city/county residents in 2017, with pre-specified targets for populations with known cancer disparities: 25% Spanish-speaking, 25% Chinese-speaking, and 25% Black Americans. Using weighted multivariable logistic regression analyses, we assessed how race/ethnicity, language preference, and having a usual place of care impacts self-report of HBV screening. Results Overall, 1027 participants completed the survey (50% of surveys administered in English, 25% in Spanish, and 25% in Chinese). Only 50% of participants reported HBV screening. In multivariable analysis, Black (OR = 0.20, 95% CI 0.08–0.49), Latinx (OR = 0.33, 95% CI 0.13–0.85), Asian (OR = 0.31, 95% CI 0.10, 0.94), and ‘Other’ race/ethnicity (OR = 0.17, 95% CI 0.05–0.53) respondents had lower odds of HBV screening compared to non-Hispanic White respondents. Participants who had insurance had increased odds of HBV screening (OR = 2.70, 95% CI 1.48–4.93). Conclusions HBV screening disparities persist for Black Americans, Asian Americans, Latinx, and the uninsured. Future studies should explore reasons why current strategies have not been implemented or are not successful, particularly in addressing racial/ethnic and insurance disparities.